Differentiation of regulatory myeloid and T-cells from adult human hematopoietic stem cells after allogeneic stimulation - Mathew, James M.; Sanders, Jes M.; Cirocco, Robert; Miller, Joshua; Leventhal, Joseph R. (Frontiers in Immunology, 2024)
Donor hematopoietic stem cell (DHSC) infusions are increasingly being studied in transplant patients for tolerance induction. To analyze the fate of infused DHSCs in patients, we developed an in vitro culture system utilizing CD34+DHSCs stimulated with irradiated allogeneic cells in cytokine supplemented medium long-term. Flow cytometric analyses revealed loss of the CD34 marker and an increase in CD33+ myeloid and CD3+ T-cell proportion by 10.4% and 72.7%, respectively, after 21 days in culture. T-cells primarily expressed TcR-αβ and were of both CD4+ and CD8+ subsets. Approximately 80% of CD3+ T cells lacked expression of the co-stimulatory receptor CD28. The CD4+ compartment was predominated by CD4+CD25+CD127-FOXP3+ Tregs (>50% CD4+CD127- compartment) with <1% of all leukocytes exhibiting a CD4+CD127+ phenotype. Molecular analyses for T-cell receptor excision circles showed recent and increased numbers of TcR rearrangements in generated T cells over time suggesting de novo differentiation from DHSCs. CD33+ myeloid cells mostly expressed HLA-DR, but lacked expression of co-stimulatory receptors CD80 and CD83. When studied as modulators in primary mixed lymphocyte reactions where the cells used to stimulate the DHSC were used as responders, the DHSC-lines and their purified CD8+, CD4+, CD33+ and linage negative subsets inhibited the responses in a dose-dependent and non-specific fashion. The CD8+ cell-mediated inhibition was due to direct lysis of responder cells. Extrapolation of these results into the clinical situation would suggest that DHSC infusions into transplant recipients may generate multiple subsets of donor “chimeric” cells and promote recipient Treg development that could regulate the anti-donor immune response in the periphery. These studies have also indicated that T cell maturation can occur in vitro in response to allogeneic stimulation without the pre-requisite of a thymic-like environment or NOTCH signaling stimulatory cell line.